ASSESSMENT OF THE STUDENTS IN PHARMACY EDUCATIONAL INSTITUTES OF LAHORE, PAKISTAN, REGARDING COVID-19 AND ITS IMPACT ON THEIR EDUCATION: AN ONLINE CROSS-SECTIONAL SURVEY - Kanwal Ashiq; Anam Yasmeen; Aneeba Ahmad; Hafiza Arbab Hussain; Rashida Perveen; Muhammad Ahmad; Abdul Hanan (International Journal of Pharmacy & Integrated Health Sciences)
Background: Globally, COVID-19 pandemic has drastically trembled day to day activities, including education. Objective: This study aims to assess students studying at pharmacy institutes that are located in Lahore, Pakistan. Methodology: An online cross-sectional survey was performed from 25th August to 25th December, 2020 in order to collect the data from students. The Statistical Package for Social Sciences (SPSS Version: 25) was used to commute descriptive statistics and independent t-test. Results: Total 471 responses were received out of which 261 (55.4%) females and 210 (44.6%) males participated in this study. The majority of population 429 (91.1%) belonged to Doctor of Pharmacy (Pharm-D) in comparison to 33 (6%) M.Phil./MS and 9 (1.9%) PhD scholars. The summary of the results with maximum response against each question is: 201 (42.7%) participants were not satisfied by e-lectures, 435 (92.4%) had internet availability, 354 (75.2%) replied they were guided before switching to online teaching, 201 (42.7%) claimed they understood e-lectures thoroughly, 420 (89.2%) faced internet and voice interruptions, 420 (89.2%) said their lab and research work got disturbed during pandemic, 261 (55.4%) were satisfied with their assessment, 273 (58%) said that pandemic had affected  their mental health and 366 (77.7%) students were optimistic and wished they could  study physically in their institutes. Conclusion: COVID-19 pandemic affects the education system in a worst possible way. Once this pandemic is over, proper policies should be developed by the government and pharmacy institutes to facilitate students regarding clinical rounds, industrial internships and retail rotations so they can perform well in their professional field.